Experimento para a estimativa da irradiância solar total: uma abordagem para o ensino médio - Gomes, Thiago do Nascimento Pereira (2019)
Energy is the most fundamental physical property in the study of science and in the understanding of the world around us. This physical quantity is often approached during the teaching of physics in areas like Thermodynamics, which concerns with the transference of energy through heat and work and its applications. In order to contextualize these concepts in classroom, we chose to discuss solar energy issues. The Sun is our main source of energy. Every second, each square meter of the atmosphere of Earth receives around 1360 J of energy from the Sun. Such value is called the total solar irradiance, which can be calculated by Stefan-Boltzmann’s law. In this work we propose an experimental activity to estimate the total solar irradiance. The experiment is simple to reproduce and makes use of easily obtainable materials. With our purpose it is possible to discuss concepts such as energy, temperature, heat, blackbody radiation, error propagation and the causes for attenuating the value of solar energy that effectively reaches the Earth's surface. Our purpose was conducted in a public school of São Paulo (Brazil) for 55 high school students. With our experiment we show the feasibility of working the scientific method and how to perform the error propagation using the collected data, demonstrating the importance of mathematics in science. Based on the engagement and motivation of the students during the execution of the experiment and the results obtained, we consider that the application of our purpose was successful. From the results obtained by the students, we updated our initial proposal to a more elaborated educational product, both experimentally and theoretically, for the calculation of the total solar irradiance through Stefan-Boltzmann’s law.